Beyond the Language Classroom
X, 208 p.
Keywords: This comprehensive exploration of theoretical and practical aspects of out-of-class teaching and learning from a variety of perspectives and in various settings around the world includes a theoretical overview of the field, 11 data-based case studies and practical advice on materials development for independent learning.